Identification of Candidate Genes and Biosynthesis Pathways Related to Fertility Conversion by Wheat KTM3315A Transcriptome Profiling - Ye, Jiali; Duan, Yang; Hu, Gan; Geng, Xingxia; Zhang, Gaoming; Yan, Pengjiao; Liu, Zihan; Zhang, Lingli; Song, Xiyue (Frontiers in Plant Science, 2017)
The Aegilops kotschyi thermo-sensitive cytoplasmic male sterility (K-TCMS) system may facilitate hybrid wheat (Triticum aestivum L.) seed multiplication and production. The K-TCMS line is completely male sterile during the normal wheat-growing season, whereas its fertility can be restored in a high-temperature environment. To elucidate the molecular mechanisms responsible for male sterility/fertility conversion and candidate genes involved with pollen development in K-TCMS, we employed RNA-seq to sequence the transcriptomes of anthers from K-TCMS line KTM3315A during development under sterile and fertile conditions. We identified 16840 differentially expressed genes (DEGs) in different stages including15157 known genes (15135 nuclear genes and 22 plasmagenes) and 1683 novel genes. Bioinformatics analysis identified possible metabolic pathways involved with fertility based on KEGG pathway enrichment of the DEGs expressed in fertile and sterile plants. We found that most of the genes encoding key enzyme in the phenylpropanoid biosynthesis and jasmonate biosynthesis pathways were significant upregulated in uninucleate, binuclate or trinucleate stage, which both interact with MYB transcription factors, and that link between all play essential roles in fertility conversion. The relevant DEGs were verified by quantitative RT-PCR. Thus, we suggested that phenylpropanoid biosynthesis and jasmonate biosynthesis pathways were involved in fertility conversion of K-TCMS wheat. This will provide a new perspective and an effective foundation for the research of molecular mechanisms of fertility conversion of CMS wheat.